Woman's Party Corporation records - Woman's Party Corporation
Chiefly records relating to the litigation between the Woman's Party Corporation and the National Woman's Party including affidavits, complaints, depositions, exhibits, interrogatories, motions, pleadings, background material, and other legal documents; photocopies of National Woman's Party bylaws and incorporation documents, correspondence, convention material, financial records, membership data, minutes, and publicity material; and dispositions and other legal material from related lawsuits.
Created by the National Woman's Party (NWP) in 1977 to collect contributions to finance the party's educational activities. In 1992, an Internal Revenue Service investigation revealed the tax-exempt corporation was providing funds to the National Woman's Party without proof that they were being used for educational purposes. The party's executive board attempted to dissolve the corporation and appropriate its assets. The corporation filed suit and the party filed countersuit, claiming breach of fiduciary responsibility. In an out-of-court settlement, the corporation was dissolved and the party agreed to become an apolitical, nonprofit, educational organization.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: National Woman's Party; Actions and defenses -- United States; Education -- United States -- Societies, etc; Nonprofit organizations -- United States; Tax exemption -- United States; Women -- United States -- Societies, etc